Simulation of biomass gasification in downdraft gasifier using Aspen Plus: article - Badrul Hayad, Khairul Zakirin; Asadullah, Mohammad (2017)
The purpose of this study is to study the simulation of biomass gasification in downdraft gasifier using ASPEN Plus and to identify the characteristics and chemical composition of biomass. To achieve this objective, the chemical and physical characteristics of biomass and how to simulate the biomass gasification process in downdraft gasifier using Aspen Plus were studied. Simulation of biomass gasification was done using Aspen Plus. The parameter that were used to study the simulation of biomass gasification using Aspen Plus were the effect of gasification temperature and air-fuel ratio towards the amount of syngas produced. It was observed that the gasification product which is syngas was dependent on the gasification temperature and the air-fuel ratio used.